THE APPLICATION OF CONSTRUCTIVISM LEARNING THEORY ON THE MOTIVATION AND QUALITY OF QUR'AN MEMORIZATION OF COLLEGE STUDENTS: Pengaruh Penerapan Teori Pembelajaran Konstruktivisme Terhadap Motivasi Dan Kualitas Hafalan Al-Qur’an Mahasiswi - Citra Marlina; Nabella Dananier (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Education is an important part in the formation of qualified andcompetitive individuals. In the educational process, learning becomesthe core that influences students to internalize the knowledge andskills taught. In an effort to improve the effectiveness of learning,learning theory becomes an important foundation to consider. One ofthem is constructivism learning theory. This study focuses on theeffect of constructivism learning theory on motivation andmemorization quality using quantitative research methods. Themotivation and quality of memorization of female students areimproved through the approach of constructivism learning theory.Female students not only focus on memorizing the Qur'an, but also onunderstanding the context and significance of these concepts.Constructivism encourages individuals to make connections betweennew concepts and prior knowledge. The sampling technique usedpurposive sampling technique from a total population of 95 and thesample taken was 75 female students of the IAI Tazkia Hafidzpreneurprogram class of 2020. The results showed that Constructivismlearning has an influence on student motivation. This is evidenced bythe sig value of 0,000 which is smaller than 0,05 and the t value of10,396 is greater than the t table value of 1,993. While in the variableof Constructivism Learning Theory with Memorization Quality, thesig value of 0,000 is smaller than 0,05 and the t value of 10,283 isgreater than the t table value of 1,993.